1997
DOI: 10.1557/jmr.1997.0292
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures and Host Excitation of LaPO4, La2O3, and AlPO4

Abstract: We report the electronic structures and associated optical properties of three inorganic oxides, namely lanthanum oxide, aluminum phosphate, and lanthanum phosphate, calculated by the first principles augmented spherical wave (ASW) and full potential linear muffin tin orbital (FP-LMTO) band structure methods, and the self-consistent field Xα scattered wave (Xα SW) molecular orbital cluster approach. Our calculations indicate negligible effect of the choice of exchange correlation potentials on the position, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 9 publications
3
12
1
Order By: Relevance
“…A binding energy of 3-4 eV for this state is in good agreement with preliminary density of state (DOS) calculations done by us, DOS calculations reported by Mishra et al 7 and qualitatively with features observed in the rather crude XPS valence-band spectra that we have been able to obtain at the present stage (Fig. 4).…”
Section: Characterization and Resultssupporting
confidence: 93%
“…A binding energy of 3-4 eV for this state is in good agreement with preliminary density of state (DOS) calculations done by us, DOS calculations reported by Mishra et al 7 and qualitatively with features observed in the rather crude XPS valence-band spectra that we have been able to obtain at the present stage (Fig. 4).…”
Section: Characterization and Resultssupporting
confidence: 93%
“…The most striking difference with previous studies can be found in the relative position of the sharp peak arising from lanthanum. While in our calculations, and in those of Mishra et al [56], the 4f peak lies about 1-1.5 eV above the bottom of the conduction band (associated to the broad La 5d peak of the DOS), in the LSDA + U calculations of Singh et al [54] this difference is around 4 eV.…”
Section: A-la 2 Ocontrasting
confidence: 46%
“…Except for the cases of La 2 TeO 6 and Y 2 TeO 6 , the electronic structure of the compounds included in this work has been studied previously using different computational approaches [45][46][47][48][49][52][53][54][55][56][57][58][59][60]. Since one of our principal aims is to obtain a general picture of the nature of the valence and conduction bands for all these compounds and its influence on the resulting optical properties, we will center our discussion on the density of states in the energy region around the band gap.…”
Section: Electronic Structurementioning
confidence: 99%
“…[1][2][3] For example, phosphate glass use in optical components is increasing, and for this the glasses are stabilized by the addition of alumina. 4,5 Aluminates figure prominently in several scientific and engineering applications, for example as support structures for optically active components in electronic systems.…”
Section: Generalmentioning
confidence: 99%
“…4,5 Aluminates figure prominently in several scientific and engineering applications, for example as support structures for optically active components in electronic systems. 2 Doping of both phosphate and aluminate glasses with rare earth elements allows tuning of the fluorescence of those elements. 2,6 Among materials for high-temperature applications, the refractory compound lanthanum-monazite (LaPO 4 ) has been intensively investigated because of its potential usefulness in * Corresponding author.…”
Section: Generalmentioning
confidence: 99%